Mutu Organoleptik Tortilla Ubi Jalar Ungu - Fitriani Basrin; Asriani Asriani; Gatot Siswohutomo (Universitas Tadulako, 2016)
This study aims: purple sweet potato tortilla has a crunchy texture. Tortilla purple sweet potato is one of a light meal that is loved by the community compared to other snacks. One of the factors that affect the quality of the tortilla is the ratio of purple sweet potato and cassava. the ratio of purple sweet potato, cassava produce purple sweet potato tortilla with good organoleptic quality. The research is designed using completely randomized design pattern combination and a randomized block design. RAL pattern combination is applied to influence the ratio of purple sweet potato and cassava (F1 = 1: 0), (F2 = 2: 1), (F3 = 2: 2), (F4 = 3: 1), (F5 = 3: 2), (F6 = 1: 1), while RAK applied in organoleptic purple sweet potato tortilla, which was tested by 30 panelists. Organoleptic quality research results purple sweet potato tortilla with panelists color value (5.33), aroma (5.03), flavor (5.97), texture (crispness) with the value (5.33) and the best level of preference is (5.27).